THE ROLE OF THE INTERNET IN PROMOTING DENTAL HEALTH AND CHANGING BEHAVIOR AMONG THE ADULT POPULATION IN IASI - Carina Balcos; Loredana Hurjui; Irina Gradinaru; Ion Hurjui; Livia Bobu; Irina Bamboi; Dana Budala; Dana Baciu; Daniela Argatu; Magda Barlean; Adina Armencia; Ramona Feier (Romanian Society of Oral Rehabilitation, 2021)
Use of the internet for obtaining relevant information regarding health is a verry common practice nowadays. The most frequent searches regard: diseases, treatments, pharmacies, and medical assistance. Aim of the study: The aim of the current study was to measure the prevalence of using the Internet as a source of oral health information among the adult population of Iasi, assessing the impact of the Internet in changing oral health behaviours and identifying barriers to using the Internet to obtain health information. Material and methods: The study involved questionnaire-based survey on 70 patients from different dental practices in Iasi. Results: The survey showed that all respondents used the internet for oral health information, Facebook being the most common application used by (53.8%) of them, followed by WhatsApp, used by (40.9%) of the respondents. Half of the participants (48.1%) considered communication with oral health professionals as one of the main advantages of using the social network to obtain information about oral health. Regarding the change in behaviour based on online oral health information, approximately (67.1%) of the respondents considered that they changed some of the oral health behaviours based on the information on social media. Conclusions: The use of internet to search for oral health information is increased. Accessibility and ease of use of the internet are the main reasons for obtaining oral health information online.